The Impact of Scientific Activity of Universities on Economic and Innovative Development - Tereshchenko, Dmitrii S.; Shcherbakov, Vasilii S. (Economy of Regions, 2021)
Universities play a crucial role in local economies, providing educational services and participating in research and development. This is particularly important for Russia where regions are highly differentiated in terms of both socio-economic development and technological progress and innovations. However, many regional universities in Russia have traditionally focused primarily on teaching, with less emphasis on research activities. In this paper, we aim to deepen the understanding of the impact of scientific activities of universities on regional economic and innovative development. For this purpose, we estimate different specifications of a fixed-effects model using panel data from Russian regions for 2010-2016. We aggregate the number of universities’ publications per researcher at the sub-national level to incorporate regional scientific activity in our model. Considering other important socio-economic characteristics of regions, we revealed that the association between the publication activity of universities and innovative development of the region remains significant, while the relationship between economic development of the region and the scientific activity of universities disappeared completely. A number of robustness checks demonstrated that statistically significant results remain only when the relative number of publications indexed in international citation databases (Scopus and Web of Science) is used as an explanatory variable. Simultaneously, the publications indexed in specific Russian lists and databases as well as publications in regional scientific organisations that are not universities do not contribute to innovative development of the region. The results can be used for planning the funding of research activities in universities and setting performance targets for universities.